DAMPAK PERUBAHAN LAHAN SAWAH MENJADI LAHAN PERMUKIMAN TERHADAP PRODUKSI PADI DI KECAMATAN KOTO TANGAH - Deni Januardi; Heny Mariati; Yulianita Yulianita (Jurnal Azimut, 2025)
This study aims to analyze the conversion of paddy fields into residential land and its impact on rice production in Koto Tangah District, Padang City. The research method used was descriptive quantitative by utilizing Landsat 8 satellite imagery from 2013 and 2024, rice production statistical data, and Geographic Information System (GIS) analysis. The research stages included image correction, land use classification, map overlay, calculation of land area changes, and estimation of rice production. The results showed that residential land area increased by 1,169.65 hectares, from 1,966.66 hectares in 2013 to 3,136.31 hectares in 2024. Meanwhile, paddy field area experienced a slight increase of 13.59 hectares, from 1,699.82 hectares to 1,713.41 hectares. The increase in paddy field area contributed to an increase in rice production of 78.82 tons. However, land use changes among villages were uneven, as several areas experienced a decline in paddy field area due to development pressure. The main factors influencing land use change were population growth, residential needs, and land economic value. Therefore, sustainable paddy field protection policies are needed to maintain regional food security